Three-dimensional cellular architecture of the flagellar pocket and associated cytoskeleton in trypanosomes revealed by electron microscope tomography. - Lacomble, S; Vaughan, S; Gadelha, C; Morphew, M; Shaw, M; McIntosh, JR; Gull, K (2009)
This study uses electron tomography linked to a variety of other EM methods to provide an integrated view of the flagellar pocket and basal body area of the African trypanosome procyclic trypomastigote. We reveal the pocket as an asymmetric membranous 'balloon' with two boundary structures. One of these - the collar - defines the flagellum exit point. The other defines the entry point of the flagellum into the pocket and consists of both an internal transitional fibre array and an external membrane collarette. A novel set of nine radial fibres is described in the basal body proximal zone. The pocket asymmetry is invariably correlated with the position of the probasal body and Golgi. The neck region, just distal to the flagellum exit site, is a specialised area of membrane associated with the start of the flagellum attachment zone and signifies the point where a special set of four microtubules, nucleated close to the basal bodies, joins the subpellicular array. The neck region is also associated with the single Golgi apparatus of the cell. The flagellar exit point interrupts the subpellicular microtubule array with discrete endings of microtubules at the posterior side. Overall, our studies reveal a highly organised, yet dynamic, area of cytoplasm and will be informative in understanding its function.